Energy expenditure and cardiovascular response to traumatic lower limb amputees' gait - Marília Mendes do Nascimento Garcia; Jorge Roberto Perrout de Lima; José Dilermando Costa Junior; Humberto Almeida Ottoni de Luna Freire; Jaqueline de Paula Mazilão; Eduardo José Danza Vicente
Introduction Amputations cause functional, musculoskeletal and cardiovascular alterations and, the more proximal the amputation, the larger the alterations. Objectives To observe the effect of using lower limb prosthetics and that of gait speed on heart rate (HR), blood pressure (BP), oxygen consumption (VO2) and energy cost (EC) during gait in traumatic lower limbs amputees. Materials and methods The sample was composed of 30 men with unilateral amputations, 10 transfemoral and 10 transtibial, compared to 10 people with no amputations. All of them selected a pleasant walking speed (PWS) on the treadmill, and two other speeds were calculated, 20% above and 20% below the original one. The subjects walked for 10 minutes at each of the speeds and, in the last three minutes, the VO2, HR, and BP were assessed. In order to compare variables between groups the variance was performed (ANOVA) followed by the Post Hoc Sheffé test (p < 0.05). Results The amputees selected lower values of PWS and had higher HR, BP, and EC, VO2 during gait when compared to normal individuals. The transfemoral amputees had higher VO2 and EC compared to the transtibial ones. By analyzing the speed effect, it was observed that, although the VO2 did not increase with the increased speed, there was increased cardiovascular response and reduced EC. Conclusions Traumatic lower limb amputees have higher energy expenditure and cardiovascular responses during gait and, at higher speeds, they become more economical, reducing the EC.